Taming Sino-American rivalry - Zhang, Feng; Lebow, Richard Ned 1942- (Oxford University Press, 2020)
"Competition between America and China has intensified since 2009, creating even greater risks of conflict. Why is this so and what can be done about it? Feng Zhang and Ned Lebow identify the mistakes China and America made in their mutual relations and explain their causes and consequences. Drawing on international relations theory and historical lessons they develop a holistic approach to conflict management and resolution. It is based on a sophisticated staging of deterrence, reassurance, and diplomacy. Minimal deterrence combined with multiple forms of reassurance and sustained diplomatic efforts to reduce or finesse key areas of conflict offer the promising pathway for America and China to enhance their security and buttress their self-esteem"--
Keywords: Außenbeziehungen; China; USA; United States / Foreign relations / China; China / Foreign relations / United States; Conflict management / United States; Conflict management / China; National security / United States; National security / China; Conflict management; Diplomatic relations; National security; United States